Penerapan Customer Satisfaction (CSAT) dalam Meningkatkan Kepuasan Pasien BPJS pada Klinik Pratama Kirana Medika Kota Bandung - Wardana Wardana; Wulan Alviena Putri Utami (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The improvement of healthcare service quality has become a significant concern within the national health insurance system, particularly for BPJS participants. This study aims to examine how the implementation of Customer Satisfaction (CSAT) contributes to enhancing BPJS patient satisfaction at Pratama Kirana Medika Clinic in Bandung City. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving 25 informants, consisting of 1 clinic PIC and 24 BPJS patients. The findings indicate that, in general, patients are satisfied with the services provided, especially in terms of staff friendliness, clarity of service procedures, ease of access, and impartiality between general and BPJS patients. However, several suggestions for improvement were noted, such as reducing waiting times and expanding the parking area. The implementation of CSAT principles has shown a positive impact on patient experience and can serve as a foundation for developing sustainable service strategies at the clinic.